2014
DOI: 10.1177/1534735414550038
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplement Use Among Patients With Hepatocellular Carcinoma

Abstract: Background. More than 50% of US adults, and an even larger proportion of cancer patients, use dietary supplements. Since many supplements require hepatic metabolism, they may be particularly likely to cause toxicities in patients with hepatocellular carcinoma (HCC). However, little is known about supplement use in patients with HCC. Methods. From 2008 to 2012, we gave newly diagnosed HCC patients at our institution a standardized questionnaire about dietary supplement use, demographic factors, and clinical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
0
9
0
2
Order By: Relevance
“…Nevertheless, a large proportion of liver disease (27 to 43%) or cancer patients (26 to 87%) use this hepatoprotective herbal-based dietary supplements hoping to improve their health and quality of life 1417 . However, although these preparations have been popularized as effective cancer preventive agents, considering the lack of clear evidence of efficacy as well as food safety 18 , a more cautious approach by consumers would be appropriate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a large proportion of liver disease (27 to 43%) or cancer patients (26 to 87%) use this hepatoprotective herbal-based dietary supplements hoping to improve their health and quality of life 1417 . However, although these preparations have been popularized as effective cancer preventive agents, considering the lack of clear evidence of efficacy as well as food safety 18 , a more cautious approach by consumers would be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the study of Lee et al . focused on measuring the prevalence of dietary supplement use by patients suffering from hepatocellular carcinoma revealed that patients who used milk thistle had marginally poorer survival than non-users did 14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that although most experimental reports and some clinical data suggest that it does play a beneficial role [8,9,10], the clinical importance of silymarin is negligible [5,7,11,12]. Moreover, the results of clinical studies conducted to date are often rather controversial and non-reproducible [7,11,13]. This is probably related to the ambiguously defined chemical composition of the silymarin complex [14] and possible contaminants [15].…”
Section: Introductionmentioning
confidence: 99%
“…En yaygın kullanılan besin takviyeleri; %51.0 oranında antioksidanlar, %46.0 multivitaminler, %25.0 D vitamini ve %23.0 deve dikeni olarak raporlanmıştır. 25 Pouchieu ve arkadaşlarının 22 yaptığı çalışmaya göre ise hastaların %28.0'i tanı ile birlikte besin takviyesi kullanımına başladıkları /bıraktıkları ya da kullandıkları besin takviyesini değiştirdikleri ve genel olarak B6 vitamini, C vitamini, magnezyum takviyelerini kullandıkları saptanmıştır. Mevcut çalışmada hastaların; %69.8'i tanı öncesi ve sonrasında vitamin/ besin takviyesi kullanmadığını, %24.1'i tanı sonrası başladığını, %4.3'ü tanıdan önce de sonra da kullandığını ve %1.7'si tanıdan önce kullandığını, tanı sonrası bıraktığını beyan etmiştir.…”
Section: Verilerin Değerlendirilmesi Ve Etik Boyutuunclassified